The hidden curriculum in islamic religious education and its impact on the character formation of Sudirman Kaliangkrik islamic high school students - Zaenal Abidin; Indah Slamet; Ita Wijayanti; Yusron Kamal (Yayasan Azhar Amanaa Yogyakarta, 2024)
Character building is one of national education purposes. This is in accordance with the contents of the 2003 National Education System Law Article 1 which states that, among the goals of national education is to develop the potential of students to have intelligence, personality and noble character. The mandate of the 2003 National Education System Law intends that education does not only form intelligent Indonesian people, but also personality or character. The Hidden Curriculum of Islamic Religious Education is a set or an unwritten plan relating to Islamic material or lessons, the objectives of the learning process, methods and approaches, as well as forms of evaluation in preparing students to know, understand, live to believe in and practice Islamic teachings in full. . This study uses descriptive qualitative methods, and data collection is carried out taken from journal documents, or other documents. Data collection by way of observation, interviews and documentation. Technical analysis of data by means of data collection, data reduction, data presentation, drawing conclusions. The application of the PAI hidden curriculum at Sudirman Kaliangkrik Islamic High School includes: (1) Memorization of short surahs, midday prayers in congregation, Kultum, Adhan, Tahlilan, Yasinan. (2) The implication of the hidden curriculum consists of two characters, namely, the first is the character of amali, seen from the congregational midday prayers, tahlilan which contains dhikr and also yasinan. The second is a cult whose goal is self-development and also learning how to preach after praying in congregation. (3) The strategy for implementing activities by providing exemplary examples to students, the application of habituation to hidden curriculum activities, and the existence of collaboration between teachers.